2011
DOI: 10.3892/or.2011.1216
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of carbonic anhydrase 9, glucose transporter-1, Ki-67 and p53 expression in oral squamous cell carcinoma

Abstract: Abstract. carbonic anhydrase 9 (cA9) is a glycoprotein present on the surface of cell membranes. It is expressed in 90% of renal cancer cells, but not in normal kidney tissue. Immunotherapy targeting cA9 is underway, and our group has also conducted a clinical trial using cA9 as a cancer vaccine and confirmed the induction of cytotoxic T lymphocytes, with efficacy in some cases. Expression of CA9 antigen in oral cancer has not been reported in Japan, but our results indicate that immunotherapy targeting cA9 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
3
15
0
4
Order By: Relevance
“…It was reported that high expression of CA9 was more frequent with lymph-node metastasis in several kinds of solid tumors including oral cancer [25], [36], [37]. In the present study, a significantly higher distribution frequency of lymph-node metastasis was exhibited in OSCC patients with at least 1 polymorphic G allele of CA9 +201 compared to those with the WT genotype (Table 6).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It was reported that high expression of CA9 was more frequent with lymph-node metastasis in several kinds of solid tumors including oral cancer [25], [36], [37]. In the present study, a significantly higher distribution frequency of lymph-node metastasis was exhibited in OSCC patients with at least 1 polymorphic G allele of CA9 +201 compared to those with the WT genotype (Table 6).…”
Section: Discussionsupporting
confidence: 59%
“…The aberrant expression of CA9 was observed in cancer cells themselves or tumor-associated stromal tissues in OSCC patients and correlated with a poor prognosis and nodal metastasis [17], [18], [25]. CA9 catalyzes the reversible hydration of carbon dioxide to carbonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Then 29 records were excluded because they lacked necessary information, did not study on OSCC patients, and were duplicate reports on the same patients or reviews. Finally, 13 studies [1117,2227] with 1301 subjects were included for meta-analysis. The flowchart of study selection was illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[9] A number of studies reported the direct link between high GLUT-1 levels and malignant conversion process. [1114,16,17,22,30] The activity of GLUT-1 was regulated by oncogenes and growth factors. [11,31] Changes of GLUT-1 levels can be influenced by growth rate, oxygen supply, and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that hypoxic tumours are generally associated with poor prognosis (Vaupel and Mayer, 2007; Jubb et al , 2010) and several groups have investigated the role of both hypoxia and proliferation in OSCC and other head and neck cancers (Ljungkvist et al , 2002; Hoogsteen et al , 2005; Kondo et al , 2011). Although a stromal CAIX and tumour Ki67 signature has not been previously explored, there is some support in the existing literature (Hoogsteen et al , 2005) for our combined hypoxia and proliferation-based prognostic signature providing a more biologically relevant definition of hypoxic tumours than sCAIX alone.…”
Section: Discussionmentioning
confidence: 99%